The Brazilian Seismographic Integrated Systems (BRASIS): Infrastructure and data management - Pirchiner, Marlon; Collaço, Bruno; Calhau, Jackson; Assumpção, Marcelo; Dourado, João Carlos [UNESP] (Instituto Nazionale di Geofisica e Vulcanologia, INGV, 2011)
In geophysics and seismology, raw data need to be processed to generate useful information that can be turned into knowledge by researchers. The number of sensors that are acquiring raw data is increasing rapidly. Without good data management systems, more time can be spent in querying and preparing datasets for analyses than in acquiring raw data. Also, a lot of good quality data acquired at great effort can be lost forever if they are not correctly stored. Local and international cooperation will probably be reduced, and a lot of data will never become scientific knowledge. For this reason, the Seismological Laboratory of the Institute of Astronomy, Geophysics and Atmospheric Sciences at the University of São Paulo (IAG-USP) has concentrated fully on its data management system. This report describes the efforts of the IAG-USP to set up a seismology data management system to facilitate local and international cooperation. © 2011 by the Istituto Nazionale di Geofisica e Vulcanologia. All rights reserved.
Keywords: data management; data processing; data quality; data set; seismic method; seismology; Brazil